Pengaruh Agroekosistem Pertanaman Kopi terhadap Keanekaragaman dan Kelimpahan Semut (Formicidae) - Susilawati, Susilawati; Indriati, Gusti (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Ant (Formicidae: Hymenoptera) is one of the dominant groups of insects and has significant biological and ecological properties. The presence of ants in coffee plantations plays an important role as it functions as a predator. The study aimed to investigate the effect of coffee plantation agroecosystem on the diversity and abundance of ant species. The study was conducted from February to June 2018 at Pakuwon Experimental Station. The coffee plants were divided into 4 groups, based on their locations and agroecosystems, where each group consisted of 4 observation plots. Ants sampling were taken from 15 sample plants in each plot.Â Â Observation was conducted on ants found in the stems, leaves, twigs and fruits of coffee plants. The ants were taken for 5 to 10 minutes from each plant. The differences in coffee agroecosystem were Â grouped based on location, altitude, coffee species, shade plant, and vegetation around the observation site. The study found 59 ant morphospecies with a total of 2,535 individuals. The dominant ant was Dolichoderus sp1. There were 4 ant species that were found in all four locations, namely Camponotus sp1., Crematogaster sp1., Dolichoderus sp1., Polyrhachis sp1. which are predatory. The analysis result showed that different coffee agroecosystem affects diversity and abundance of ants.